Formulation And Evaluation Of Sustained Release Tablets Using Natural Polymer - Sharma, Puneet; Rana, Ritesh; Devi, Priyanka; Kumar, Sahil (Journal of Neonatal Surgery, 2025)
Utilizing isolated biocompatible Tamarind gum (TG) as a binder, a sustained-release (SR) tablet of Aprepitant was formulated. The pre-compression properties of the wet granulated granules were found to be within the official standard range, indicative of their free-flowing nature. The tablets of Aprepitant with extended release were made using wet granulation. Following compression, the generated tablets were examined for quality control tests and the outcomes fell within the authorized official range. Given that the FT-IR spectra showed no additional peaks, it demonstrated that the drug and TG did not interact chemically. Following an in-vitro release investigation, formulation AF4 was determined to be the optimal formulation. The stability studies verified that the produced tablet form,ulation maintained its original form indicating the tablet's stability.